2019
DOI: 10.1073/pnas.1819047116
|View full text |Cite
|
Sign up to set email alerts
|

Blind tests of RNA–protein binding affinity prediction

Abstract: Interactions between RNA and proteins are pervasive in biology, driving fundamental processes such as protein translation and participating in the regulation of gene expression. Modeling the energies of RNA-protein interactions is therefore critical for understanding and repurposing living systems but has been hindered by complexities unique to RNA-protein binding. Here, we bring together several advances to complete a calculation framework for RNA-protein binding affinities, including a unified free energy fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 48 publications
(58 reference statements)
0
24
0
Order By: Relevance
“…These results were supported by bioinformatics prediction of 2D or 3D structure, and the functional experiments including co-localization of ISH and IF, RNA pull-down assays. Although this regulation pattern of RNA-protein interaction had been widely investigated [ 46 48 ], however, no study was reported between ZFAS1 and DDX21 in regard to cancers. In osteosarcoma, ZFAS1 was observed directly interacting with ZEB2 protein and then regulated the stability of ZEB2, thereby leading to increased cell growth and metastasis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results were supported by bioinformatics prediction of 2D or 3D structure, and the functional experiments including co-localization of ISH and IF, RNA pull-down assays. Although this regulation pattern of RNA-protein interaction had been widely investigated [ 46 48 ], however, no study was reported between ZFAS1 and DDX21 in regard to cancers. In osteosarcoma, ZFAS1 was observed directly interacting with ZEB2 protein and then regulated the stability of ZEB2, thereby leading to increased cell growth and metastasis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some examples of applications in bioinformatics (more information can be found in the reference therein) include the prediction of residue solvent accessibility, 1 protein folding kinetics, 2 protein stability changes on residue mutations, 3,4 protein affinity changes on residue mutations, 5,6 and binding affinity between RNA and protein molecules. 7 Given that all prediction methods exploit data that may contain a broad range of experimental variability, an estimate of the theoretical upper bound for the prediction is crucial for the understanding and interpretation of the results.…”
Section: Short Commentarymentioning
confidence: 99%
“…The outcome of RNA-protein interaction is likely to provide some key insights into these open questions. More generally, the link between the cellular level that is addressed by viral kinetics modeling and the molecular level of examining primary and secondary structures of the RNA molecule might be more thoroughly understood by the prediction of RNA-protein interactions, a computational sub-field that has been developed in recent years and is actively being pursued these days, e.g., [65][66][67].…”
Section: Discussionmentioning
confidence: 99%